Effects on valence, arousal and emotions in learning across different realism designs of 2d virtual agents - Vicneas Muniady (Tanjong Malim, 2020)
Effects on valence, arousal and emotions in learning across different realism designs of 2d virtual agents by Vicneas Muniady